Perbedaan Hasil Belajar Pada Mata Pelajaran Pendidikan Agama Islam (PAI) Berdasarkan Keaktifan belajar Siswa Kelas X SMA Swasta Al-Hidayah Medan. - Mavianti . (Intiqad: Jurnal Agama dan Pendidikan Islam, 2019)
This research aims to a. know the learning outcomes on the subjects of Islamic Religious Education (PAI) based on the liveliness of class X students of SMA Al-Hidayah Medan. b. knowing the learning outcomes in the subjects of Islamic Religious Education (PAI) based on inactivity of students of class X SMA Al-Hidayah Medan. c. know the difference of learning result on the subjects of Islamic Religious Education (PAI) based on the activity and inactivity of the students of grade X SMA Al-Hidayah Medan. This research is quantitative research, population in this research amount to 120 student of class X SMA Al-Hidayah Medan. While 60 people using cluster random sampling. The result of hypothesis test shows that: 1. The result of student learning that actively follow religious learning activity is high, with the average value of student learning is 7.45, while the learning result of students who are not actively follow the learning activity of religion is enough, average 6.05. 2. There are differences in student learning outcomes that actively participate in learning activities with those who are not actively participating in religious learning activities. This is evident from the results of the hypothesis calculation is >  or 1.92 > 1.66 at a significant level of 5% (0.05). 3. The difference of religious learning outcomes of active students with inactive indicates that teacher role is very important to find solution to improve student learning result especially for those who are not active follow religion subject.